[tex]\displaystyle\bf\\\sqrt{\Big(\sqrt{23} -7\Big)^{2} } -\sqrt{\Big(\sqrt{23}-3\Big)^{2} } =\Big|\sqrt{23} -7\Big|-\Big|\sqrt{23} -3\Big|=\\\\\\=7-\sqrt{23} -\Big(\sqrt{23} -3\Big)=7-\sqrt{23} -\sqrt{23} +3=10-2\sqrt{23}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\\sqrt{\Big(\sqrt{23} -7\Big)^{2} } -\sqrt{\Big(\sqrt{23}-3\Big)^{2} } =\Big|\sqrt{23} -7\Big|-\Big|\sqrt{23} -3\Big|=\\\\\\=7-\sqrt{23} -\Big(\sqrt{23} -3\Big)=7-\sqrt{23} -\sqrt{23} +3=10-2\sqrt{23}[/tex]